The Role of the Civil Service Police Unit in Creating Order for Street Vendors (PKL) in Galuh Mas, Karawang - Shifa Awiah; Dewi Noor Azijah; Lukmanul Hakim (Peneliti.net, 2022)
As life develops very rapidly, the number of street vendors (PKL) is increasing day by day, so that more and more street vendors violate Regional Regulations. Street vendors often disturb public order, beauty and order. Therefore, the role of the Civil Service Police Unit is urgently needed in realizing security, peace and order. The theory in this study is based on the role theory according to Jones (in Zulpiansyah, 2019), including the role criteria as Regulatory Role (Policy Planner), Enabling Role (Policy Implementer) and Direct Role (Policy Supervisor). The research method used is descriptive qualitative. The results showed that the role of Satpol PP Karawang: Regulatory role, its advantages include: (1) the implementation of tasks has followed the applicable Standard Operating Procedures (SOP), (2) there is a schedule of routine activities or routine patrol schedules every month. The role of the Karawang Satpol PP as an enabling role, its weaknesses include: (1) the attitude of the officers in carrying out enforcement is less persuasive, (2) the coordination is not optimal because it is not carried out formally through work meetings. The role of the Karawang Satpol PP as a direct role includes: (1) routine patrol activities are just routine because they do not make direct appeals to street vendors (2) Karawang Satpol PP officers rarely communicate with street vendors, (3) Street vendors do not submit complaints and suggestions to the Karawang Satpol PP.